Exploring the Significance of Art in Writing: A Qualitative Study - Liew, Zheng; Tan, Mae (CV TOPAZART, 2024)
This study explores the critical role of art in the realm of writing, highlighting the transformative impact of artistic elements on the written word. Art infuses writing with creativity, beauty, and depth, transcending mere communication to become a form of expression that engages readers on emotional, intellectual, and aesthetic levels. Through the use of metaphors, symbolism, vivid imagery, and figurative language, writers create narratives that captivate, convey complex ideas, and provoke introspection. Artful writing, found in various genres like fiction, poetry, and creative non-fiction, goes beyond storytelling; it resonates with readers, leaving a lasting impression and enriching the written word with its unique artistic charm. This study use qualitative approach, through in-depth interviews and surveys, with a diverse group of participants, including writers, readers, educators, and professionals from various fields. The result finings show the integral relationship between art and writing, emphasizing how art elevates writing to a higher form of human expression, connecting hearts and minds through the power of language, including the important think art in writing processing, and the ability to work under pressure.